Investigating polymorphisms in genes encoding TGF-β1, IL-10, and IL-6 and their associations with type 1 diabetes mellitus - Ahmed H Alghamdi; Mohamed F El-Refaei; Ibrahim M Shatla; Sherif M El-Sherbini (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2023)
Many cytokines play a role in the pathogenesis of Type 1 Diabetes (T1D), and gene polymorphisms could possibly contribute to the disease's genetic predisposition because they can affect cytokine production or function. The purpose of this study was to investigate the role of the gene polymorphisms TGF-β1 (+869T/C), (+915G/C), IL-10 {-1082 G/A), (-819 C/T), and (-592 A/C), and IL-6 (-174 G/C) in hereditary vulnerability to T1D. The Polymerase Chain Reaction with Sequence-Specific Primers (PCR-SSP) was used to analyze the polymorphisms. According to their genotypes, individuals were divided into the low-, high-, or intermediate-producer phenotypes predicted for these cytokines polymorphisms. Our findings revealed that the production of TGF-β1 was significantly higher in control than in T1D participants whereas the IL-6 genotype with low IL-6 production was significantly increased in the cases compared to the control. A significant association was evident between TGF-β1 and IL-6 low production and the incidence of T1D, thereby confirming the importance of TGF-β1 and IL-6 polymorphism as a genetic factor contributing to the incidence of T1D. By contrast, the involvement of IL-10 in the incidence of T1D was not as clear. Although some evidence supports a relationship, no statistically significant association has been verified between IL-10 and T1D. This type of measurement could be beneficial in determining the susceptibility and severity of the T1D condition while also taking into consideration the prediction of T1D incidence.